Terrestrial Vegetation Management Expert System (ES) Prototype for Environmental Impact Assessment (EIA) - Sehkaran, Vikneswaran Nair (1998)
The tropical rainforest of Malaysia holds one of the richest flora in the world. The favourable climate has produced flora of amazing richness and variety. Terrestrial vegetation of tropical rainforests is an important feature of the environment. Plants play a major role in the environment. Conservation of a particular environment depends fundamentally on the maintenance of existing plants and their communities and hierarchies. Therefore, the application of a computer technology in the form of an expert system (ES) will be able to help in the analysis and management of the EIA information. The ES is named VEGEVIC. A rule-based system is developed to guide the user in producing an EIA report. Knowledge for this system is elicited from the domain expert through interviews, existing literature and EIA reports between 1995 and 1997. Application of the system will lead to greater consistency in producing a standard approach when preparing an EIA report.